O15 Secondary stroke lesion growth in the follow-up after endovascular therapy: a prospective longitudinal imaging study. (29th August 2022) - Berndt, M; Kathleen, B; Hernandez Petzsche, M; Henze, S; Maegerlein, C; Zimmer, C; Wunderlich, S; Ikenberg, B; Boeckh-Behrens, T
Abstract : Introduction: Clinical outcome of endovascular treated stroke is dependent on multiple variables, resulting in a large inter-individual variability. In this context, secondary stroke injury might be of relevance but has not been systematically investigated yet. Aim of the study was to uncover secondary phenomenon in follow-up-imaging and identify possible underlying reasons. Methods: In a prospective, longitudinal single-center study endovascular treated patients were included and followed-up after 3 to 12 months by clinical and imaging investigations. Stroke lesions were segmented, microstructural alterations were assessed by analyzing DTI-metrics and associations to clinical parameters were investigated. Results: Within the cohort (n=81), 25 patients (31%) are identified with lesion growth (LG) in the follow-up-imaging, either adjacent to primary stroke lesion or distant. DTI-metrics show a partially reversible loss of microstructural integrity. An underlying vascular pathology is identified for 72% of LG patients (vs.39%, p<0.01), including an acute carotid pathology and/or a persisting stenosis in the follow-up. None of the LG patients present with new clinical symptoms, but the LG-group shows a lower rate of neurological improvement (p<0.01) and higher follow-up-NIHSS-values (p=0.03), which is mediated by ischemic volume. Conclusions: The phenomenon of lesion growth in the follow-up with microstructural changes is newly described for a high proportion of endovascular treated stroke patients. Of note, the described lesions are predominantly localized in the white matter within the deep watershed zone. Underlying reasons for the secondary injury may be multifactorial, but the association to underlying vascular pathologies directs to a possible connection to disturbed vascular autoregulation functions. Do you have any conflict of interest to declare? : No